Facilities in Asia for future accelerator development. (1st June 2022) - Kando, M.; Hosokai, T.; Kim, K.Y.; Tang, C.
Abstract: We introduce and review available and active research facilities that involve novel acceleration concepts in Asia. Most of the facilities equip with high-peak-power (>10 TW) lasers with tens of femtosecond duration for laser wakefield acceleration. The activities in Asia are growing and several problems on the realization of high energy frontier accelerators would be accessed through the existing facilities.